Functionalized 3D Architected Materials via Thiol-Michael Addition and Two-Photon Lithography - Yee, Daryl W (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.